In vitro Osmotic Stress Memory in Chrisanthemum hybridum: Structural and Physiological Responses (Plant Tissue Culture and Biotechnology, 2017)
Structural and physiological responses of chrysanthemum to repeated osmotic stress were studied. Plants were cultured for 2 weeks (for each stress1 and stress 2) on half MS supplemented with mannitol 100 mM (Treatment I) and 200 mM (Treatment II). First stress inhibited growth parameters stronger than second stress in treatment I. In treatment II both stress events strongly inhibited growth parameters of micro‐shoots. Proline content exceeded control 6 ‐ 8 times after 1st stress, and 2 ‐ 5 times after the 2nd stress in treatments I and II, respectively. Soluble protein was accumulated in leaves during both stress exposures, and 2 ‐ 2.5 times exceeded control after the 2nd stress. Relative water content in both treatments increased after the 2nd stress exposure. In treatment II chlorophyll а and carotenoids contents were 8.78 and 4.62 mg/g comparing to control (4.21 and 2.25 mg/g, respectively) after the 1st stress. But after the 2nd stress there was no difference with control.Plant Tissue Cult. & Biotech. 27(2): 161-169, 2017 (December)